Contextual and individual factors associated with dissatisfaction with the Brazilian Unified National Health System, 2011-2012 - Lúcia Gimenes Passero; Jessye Melgarejo do Amaral Giordani; Fernando Neves Hugo; Vanessa Bielefeldt Leotti Torman; Suzi Alves Camey; Juliana Balbinot Hilgert
Abstract: User satisfaction is known to be related to quality of healthcare. The aim of this study was to evaluate the influence of contextual and individual factors associated with user dissatisfaction with the Brazilian Unified National Health System (SUS). This was a cross-sectional multilevel study. Data were collected via telephone by the ombudsman's office of the SUS. Telephone numbers were randomly selected from a telephone company database. Health services, socioeconomic, and individual demographic variables were evaluated, in addition to information on the municipalities. The outcome variable was dissatisfaction with the SUS. Hierarchical multilevel logistic regression was used, and 18,673 individuals were contacted. Prevalence of dissatisfaction was 63.4% (95%CI: 62.7-64.1). Unmet demand (OR = 3.66), waiting time > 4 hours (OR = 2.82), and number of Primary Healthcare Units (OR = 0.89) were associated statistically with dissatisfaction. Characteristics of the health teams' work process showed a strong association with dissatisfaction.